Content characteristics of the entrepreneurship-based curriculum in Iran's education system - Nairi, Amir Reza; Mehdizadeh, Amir Hossein; Nourian, Mohmmad; Ismailzadeh, Zohreh; Sharifian, Leila (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: The changes brought about by globalization, technological advancements, and the dynamics of the job market in the 21st century have impacted education. Educational systems in various countries are seeking the best methods to educate children and adolescents in their daily and professional lives, considering the requirements of the 21st century. The purpose of this research was to identify the characteristics of entrepreneurship-based curriculum content in the secondary education system in Iran. Methods: The research was applied in nature and qualitative in methodology. To this end, interviews were conducted with 25 experts who were well-versed in the research topic, using purposeful sampling of a judgmental type, until theoretical saturation was achieved. For the analysis of the qualitative part, the three coding processes of open, axial, and selective coding by Strauss and Corbin were employed. Results: The results of the data analysis showed that the characteristics of entrepreneurship-based curriculum content in the secondary educational system in Iran include: designing diverse and active curriculum content (1- inspiring curriculum, 2- practicality of curriculum content, 3- quality curriculum content). Developing curriculum content aimed at educating entrepreneurial citizens (1- learning about oneself, 2- entrepreneurial knowledge, 3- skill-focused curriculum content, 4- learning about the environment and entrepreneurial networks). The third is aligning curriculum content with societal needs and scientific developments (1- ethics of entrepreneurship, 2- adapting curriculum content to changes, 3- preparing students for the business world with awareness). Emphasizing student activity in the curriculum through practical exercises and creating personal experiences (1- student competency in time management, 2- the presence of practical exercises, 3- student ability to think about starting a business). Conclusion: Educating entrepreneurial citizens is an urgent need in today's society as today's student is expected to have a professional life in the future and step into the world of work. Therefore, it is necessary for the curriculum content to align with global changes and transformations, equipping students to be competent and skill-focused individuals.